85P Impact of digital patient monitoring (DPM) on quality of clinical care of cancer immunotherapy (CIT)-treated patients (pts) with advanced/metastatic non-small cell lung cancer (a/mNSCLC). (15th December 2019) - Schmalz, O O; Jacob, C; Ammann, J; Liss, B; Iivanainen, S; Kammermann, M; Koivunen, J; Giger, M; Klein, A; Popescu, R A
Abstract: Background: Pts with cancer have disease- and treatment-related symptoms. DPM can facilitate outpatient symptom detection and improve clinical practice, pt quality of life and health benefits. We assessed pt/healthcare professional (HCP) adoption and clinical impact of a DPM tool in CIT-treated pts with a/mNSCLC. Methods: Literature research and pt/HCP advisory boards identified factors influencing DPM use and CIT-related symptoms. These were used to develop a drug-/indication-specific CIT pt module for the Kaiku Health DPM platform, encompassing a symptom questionnaire (per National Cancer Institute Common Terminology Criteria for Adverse Events), HCP symptom overview/alerts, direct pt–HCP communication and pt education for mild/moderate symptoms. The DPM tool was tested over 3 months in Switzerland, Finland and Germany (10 clinics; 45 pts; 2L+ CIT monotherapy). User experience, overall satisfaction and clinical practice impact data from an online survey/HCP interviews were analysed quantitatively/qualitatively. Results: Of the 21 pt/27 HCP online survey respondents, 73% rated themselves as competent/proficient/expert and 85% used the tool at least weekly; 60% for ≤ 10 min per week (pts)/day (HCPs). Most agreed that the tool facilitated more focused and efficient communication. Preferred functions by pts and HCPs were drug-specific information and symptom alerts, respectively. The table shows time needed for pt tool introduction and HCP time saved per pt visit. Telephone consultation need decreased for 33% of pts. Continuous monitoring led to earlier CIT symptom management in several pts. Tool expectations were met/exceeded for 89% of HCPs. Conclusion: The DPM tool educated and empowered pts and saved time on symptom reporting. It also improved care quality, efficiency and pt–HCP communication and enabled earlier symptom management, highlighting the contributions of DPM to clinical care. Editorial acknowledgement: Support for third-party writing assistance for this abstract, furnished by Katie Wilson, PhD, of Health Interactions, was provided by F. Hoffmann-La Roche Ltd, Basel, Switzerland. Legal entity responsible for the study: F. Hoffmann-La Roche Ltd, Basel, Switzerland. Funding: F. Hoffmann-La Roche Ltd, Basel, Switzerland. Disclosure: O.O. Schmalz: Advisory / Consultancy, Payment planned: F. Hoffmann-La Roche Ltd; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche Ltd. C. Jacob: Advisory / Consultancy, External consultant to lead the study design, data analysis, and reporting: F. Hoffmann-La Roche Ltd; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche Ltd. J. Ammann: Shareholder / Stockholder / Stock options, Full / Part-time employment: F. Hoffmann-La Roche Ltd; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche Ltd. B. Liss: Advisory / Consultancy, Payment planned: F. Hoffmann-La Roche Ltd; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche Ltd. S. Iivanainen: Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Advisory / Consultancy, Travel / Accommodation / Expenses: MSD; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses, Lecture: Boehringer Ingelheim; Travel / Accommodation / Expenses: Novartis; Travel / Accommodation / Expenses: Kaiku Health; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche Ltd. M. Kammermann: Full / Part-time employment, Part-time contractor: F. Hoffmann-La Roche Ltd; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche Ltd. J. Koivunen: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: MSD; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Novartis; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Pfizer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Pierre Fabre; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: Roche; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Takeda; Advisory / Consultancy, Travel / Accommodation / Expenses: Faron; Advisory / Consultancy, Travel / Accommodation / Expenses: Kaiku Health; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche Ltd. M. Giger: Honoraria (self): F. Hoffmann-La Roche Ltd; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche Ltd. A. Klein: Shareholder / Stockholder / Stock options, Full / Part-time employment: F. Hoffmann-La Roche Ltd; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche. R.A. Popescu: Advisory / Consultancy, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy: Merck Sharp & Dohme; Advisory / Consultancy: Merck; Advisory / Consultancy: Lilly; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Vifor Pharma; Advisory / Consultancy: Nutricia; Research grant / Funding (institution): Sanofi; Research grant / Funding (institution): AbbVie; Non-remunerated activity/ies, Third-party medical writing assistance, furnished by Katie Wilson, PhD, of Health Interactions: F. Hoffmann-La Roche Ltd.